If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying j + -8 = 9 Reorder the terms: -8 + j = 9 Solving -8 + j = 9 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + j = 9 + 8 Combine like terms: -8 + 8 = 0 0 + j = 9 + 8 j = 9 + 8 Combine like terms: 9 + 8 = 17 j = 17 Simplifying j = 17
| X/7=84 | | 7+1/5x0 | | 4=-1+x | | 2y-4/x | | -8x+6x-2x=0 | | y=.5x+25 | | 5x-50=4x-10 | | 11/59=x/70 | | 11/59=x/70 | | 32x^2-28x+15=0 | | 4/5x=2/3(x+6) | | -16=n-8 | | 1/7(2x-3)=3 | | 4t-13=2t+9 | | 0.7c-10=.5 | | 11x-11=8x+19 | | r/3=5 | | m^2-2m/m-2 | | 2m^2(-3m+4m^2)-(9m)= | | 2m^2(-3m+4m^2)-(3m)= | | 6x+15y=2013 | | -63=-9*s | | 4(-2x+6)=-16 | | 14t-4=11t+5 | | 0.5x^2-5=5 | | h-9=13 | | -45m++68=84m-61 | | 15x-4=8x+3 | | 3x+2y=140 | | -32x^2-28x+15=0 | | 5y-15y=50 | | -75=3*v |